Complex radial diagnostics of hemodynamic changes in long term period after Ross procedure - Klymyshyn, Y. I.; Romanyuk, O. N.; Lebid, I. G.; Artemenko, E. A.; Dzyurman, D. O. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Echocardiographic diagnosis can effectively assess the immediate and long term results after Ross operation and find the causes of reinterventions. The complex radial diagnostics was performed in 174 of 200 patients who had Ross procedure during the period from 1996 to 2002 in Institute of Cardiovascular Surgery of the Academy of Medical Sciences of Ukraine and from 2003 to 2015 in UCCC. With Echocardiography method evaluated the immediate and long-term results. Overall postoperative mortality was 8.9% (17 patients). Freedom from RV-PA conduit reoperation after 15 was 85.1%, freedom from balloon angioplasty of RV-PA conduit afer 15 was 86.7%. Fifteen-year freedom from reoperation on autograft in this group of patients has reached 95.6%. Our research prove good immediate and satisfactory long-term results of Ross procedure.